Composite zein - propylene glycol alginate particles prepared using solvent evaporation: Characterization and application as Pickering emulsion stabilizers. (December 2018) - Dai, Lei; Zhan, Xinyu; Wei, Yang; Sun, Cuixia; Mao, Like; McClements, David Julian; Gao, Yanxiang
Abstract: There is great interest in identifying biopolymer-based particles to stabilize Pickering emulsions. Pure zein particles are easy to fabricate but are unsuitable for this purpose because of their high hydrophobicity. In this study, composite zein - propylene glycol alginate particles (ZPGAPs) were prepared using a solvent evaporation method. The potential of using these particles to stabilize oil-in-water emulsions through a Pickering mechanism was also studied. ZPGAPs prepared at a zein-to-PGA mass ratio of 10:1 had considerably smaller particle diameters (346 nm) than those prepared using pure zein (1400 nm) as determined by light scattering and scanning electron microscopy (SEM). The interface wettability of ZPGAPs mainly depended on the zein-to-PGA mass ratio. The three-phase contact angle ( θ ) of pure zein particles was around 68.1° whereas that of ZPGAPs was around 90°, suggesting that the composite particles had suitable wettability characteristics for stabilizing Pickering emulsions. Confocal laser scanning microscope (CLSM) images showed that ZPGAPs formed a densely packed layer around the surfaces of the oil droplets, further highlighting the potential of the composite particles as emulsion stabilizers. The elastic modulus (G′) was higher than the loss modulus (G″) in all the Pickering emulsions, which was indicative of the formation of an elastic gel-like structure. The rheological properties of the Pickering emulsions could be modulated by altering the composite particle concentration, droplet concentration, ionic strength, pH, and temperature. These results suggest that the ZPGAPs developed in this work may be a promising stabilizer of Pickering emulsions and may extend the application of zein in food products. Graphical abstract: Highlights: Composite zein-PGA particles (ZPGAPs) were prepared using a solvent evaporation method. ZPGAPs had suitable wettability characteristics for stabilizing Pickering emulsions. ZPGAPs formed a densely packed layer around the surfaces of the oil droplets. All the obtained Pickering emulsions formed an elastic gel-like structure. The rheological properties of the Pickering emulsions could be modulated.